Complex partial non-convulsive status epilepticus masquerading as hepatic encephalopathy: a case report - Badshah, Maaz B (BioMed Central, 2012)
INTRODUCTION: Hepatic encephalopathy is usually suspected in patients who are cirrhotic with neuropsychiatric manifestations. We present a case of suspected hepatic encephalopathy that did not respond to standard empiric therapy and was eventually diagnosed as non-convulsive status epilepticus of complex partial type. Our patient responded dramatically to anti-convulsive therapy. CASE PRESENTATION: We report the case of a 45-year-old African-American man with hepatitis C virus cirrhosis and human immunodeficiency virus who presented to our facility with a one-day history of confusion and a variable mental status. Our patient’s vital signs were stable and all his electrolytes were within normal range. A clinical diagnosis of hepatic encephalopathy was made and our patient was started on empiric therapy with lactulose and rifaximin. Our patient did not respond to therapy. After five days of treatment, alternative diagnoses were sought and a neurology consult was requested. An electroencephalogram was eventually performed which showed seizure activity in the right parietal lobe. A diagnosis of non-convulsive status epilepticus was made and our patient was started on oral levetiracetam. On day two of therapy, our patient was alert and oriented. He continues to do well on follow-up approximately one year after discharge. CONCLUSIONS: Non-convulsive status epilepticus should be considered in the differential diagnosis of patients with suspected hepatic encephalopathy who do not respond to empirical treatment. Further studies are needed to investigate the incidence of this entity in patients with persistent hepatic encephalopathy.